Crenças de professores sobre o uso de tecnologias na sala de Língua Inglesa: um estudo de caso - Milhomem, Kellinne Silva (Universidade Federal do Tocantins, 2020)
The present course conclusion paper has the aim at investigating some beliefs about the use of Information and Communication Technologies in an English classroom through a case study. The specific objectives are to identify how the use of technology can provide improvements in teaching; citing teacher beliefs about language teaching and learning; check the impression of teachers in including technology in their classes. Given the need of inserting technology in the classrooms, since as known, its benefits students` output and commitment, we anchor BARCELOS (2007), KUMARAVADIVELU (2006), LEFFA (2006), PAIVA (2017), ROJO (2013) e SILVA (2007). This is a qualitative approach, having two teachers from a public school in Araguaína, Tocantins interviewed. Were used surveys containing open and closed questions, and the results have led us to a reflection about the use of technologies in English classrooms, mainly to the importance of teachers teaching training in this area.